How air temperature affects flight initiation distance in arid-zone birds - Pistorius, Penny (Percy FitzPatrick Institute of African Ornithology, 2016)
Arid zones, such as the Kalahari in southern Africa, are experiencing an increase in the number of hot days, as well as in the intensity of heat waves. Research is being conducted to try and understand how increasing temperatures will impact bird communities and population persistence in these areas. Understanding the mechanisms through which birds are vulnerable to climate change is key to answering these questions. This study investigated how changes in air temperature affect arid-zone birds' response to predators. The flight initiation distances (FID), i.e. the distance from a predator when the prey initiates escape, of eight bird species in the Kalahari were measured over a range of air temperatures during October and November 2015. The results from this study show a negative relationship between air temperature and FID. This relationship was weak across the full range of temperatures observed during the study period (11.9 ⁰C - 40.4 ⁰C), with a large amount of variability in FID not explained by air temperature. However, high air temperatures (> 35 ⁰C) were important in explaining some of the variation in FID. Starting distance, time of day, bird species, plant species, bird location (on the ground / in the canopy / at the top of the tree / in a dead tree), bird exposure (whether the bird was in the sun or in the shade) and bird activity (whether mobile / stationary) were consistently found to explain some of the variation in FID in this dataset. The relationships between the behavioural variables (plant species, bird location, bird exposure and bird activity) and air temperature were investigated and revealed a potential mechanism through which air temperature may also indirectly be affecting FID. The reduction in FID at high air temperatures, and thus the potentially increased risk of predation, may have negative consequences for these species in the Kalahari in light of rising air temperatures associated with climate change